A new and generalized structure of single‐phase and three‐phase cascaded multilevel inverter with reduced power components. (1st September 2019) - Mahato, Bidyut; Majumdar, Saikat; Jana, Kartick Chandra
Summary: The proposed work shows a novel multilevel inverter (MLI) configuration to generate a large number of voltage levels with lesser number of power switches. The proposed generalized inverter comprises basic cells cascaded to each other. Each cell of the proposed inverter can generate three‐level AC voltage using the power switches of the same rating. Both single‐phase and three‐phase MLI configurations are possible for the proposed structure. To validate the performance of the proposed MLI configuration, a nine‐level inverter using six power switches and a 27‐level inverter using nine power switches are designed and simulated in the MATLAB/Simulink environment. An experimental prototype is developed in the laboratory, and the experimental results are presented to verify the simulated results. Further, to validate the effectiveness of the proposed multilevel inverter, a comparison of the proposed MLI with recently proposed multilevel inverter has been incorporated in a detailed manner.